Long-term testosterone replacement therapy reduces fatigue in men with hypogonadism - Maurício de Almeida Ferreira; José Alexandre Mendonça (Drugs in Context, 2022)
Background: Testosterone replacement therapy (TRT) is one of the main lines of treatment for men with hypogonadism. This study sought to evaluate the influence of TRT in men with late-onset hypogonadism (LOH), regarding fatigue, coronary artery disease (CAD), carotid intima-media thickness (CIMT) and cardiovascular risk.